2014
DOI: 10.1166/jbn.2014.1756
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-Staphylococcal Activity of TiO<SUB>2</SUB> Nanoparticles and Nanowires in <I>Ex Vivo</I> Porcine Skin Model

Abstract: Staphylococcus aureus is one of the major causes of skin and soft tissue infections. In this study we compared the antimicrobial activity of two different TiO2 nanoformulations against Staphylococcus aureus. We synthesized TiO2 nanoparticles of approximately 80 nm diameter and TiO2 nanowires of approximately 100 nm diameter. Both nanoformulations possess anti-microbial activity; were non-hemolytic and cytocompatible. However, the anti-staphylococcal activity of TiO2 nanowires was better than the nanoparticles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 25 publications
3
23
0
Order By: Relevance
“…121 In addition, the potential of the bacterial cell membrane plays an important role in cell communication, which has a close relationship with apoptosis. For example, the disruptive effect of TiO 2 NPs on the potential of the bacterial cell membrane was measured by fluorescence microscopy, 122 and changes in the fluorescence intensity of the cytoplasm were observed when altering the potential of the cell membrane.…”
mentioning
confidence: 99%
“…121 In addition, the potential of the bacterial cell membrane plays an important role in cell communication, which has a close relationship with apoptosis. For example, the disruptive effect of TiO 2 NPs on the potential of the bacterial cell membrane was measured by fluorescence microscopy, 122 and changes in the fluorescence intensity of the cytoplasm were observed when altering the potential of the cell membrane.…”
mentioning
confidence: 99%
“…Extent of hemolysis was determined according to previously described method [21]. Briefly 1 ml blood was diluted 10 times with Ringer buffer.…”
Section: Determination Of Hemolysismentioning
confidence: 99%
“…The antibacterial effects of Ag-based NWs (Holtz et al 2010(Holtz et al , 2012Jiang et al 2012;Liu et al 2013;Schoen et al 2010;Singh et al 2014;Tamboli et al 2012;Tang et al 2014;Visnapuu et al 2013;Zhang et al 2007), Si NWs (Lv et al 2010), ZnO NWs (Kılıç and Omay 2014;Wu et al 2011), MgO NWs (AlHazmi et al 2012, Mn 2 O 3 NWs (Hassan et al 2012), Tibased NWs (Nataraj et al 2014;Shang et al 2010), and CdO NWs (Kumar and Ojha 2013) were evaluated. Test subjects included the pathogenic bacteria species Escherichia coli, Bacillus subtilis, Staphylococcus aureus, …”
Section: Toxicity Of Nanowires To Bacteriamentioning
confidence: 99%
“…Nataraj et al (2014) NWs were also observed to disrupt E. coli cell membranes and to cause leakage of intracellular contents in a study that used TEM analysis (Hassan et al 2012). According to Zhang et al (2007), the effects of Ag NWs on bacteria may be similar to those of Ag, which has strong antibacterial activity and inactivates bacterial proteins by interacting with the -SH group in the bacterial protein molecules.…”
Section: Toxic Mechanism Of Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation